Efektivitas Model Pembelajaran Terintegrasi Problem Based Learning dan Group Investigation terhadap Kemampuan Berpikir Kritis dan Kolaborasi Mahasiswa pada Mata Kuliah Pemberdayaan Perempuan dan Lansia - Debi S. Fuadi; Dwi Ismawati; Lazfihma Lazfihma; Dwi Lyna Sari (Universitas Negeri Padang, 2026)
This study aims to analyze the effectiveness of the Problem Based Learning–Group Investigation (PBL–GI) learning model on students’ critical thinking and collaboration skills in the Women and Elderly Empowerment course. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The research subjects consisted of two groups: an experimental group that implemented the PBL–GI model and a control group that used conventional learning methods. The research instruments included a critical thinking test and a collaboration observation sheet. Data analysis was conducted using normality and homogeneity tests, t-test, as well as N-Gain and effect size calculations.The results showed that there was a significant difference between the experimental and control groups. The experimental group experienced a higher improvement in critical thinking and collaboration skills compared to the control group. The N-Gain value of the experimental group was in the moderate to high category, while the effect size indicated a strong influence. These findings demonstrate that the PBL–GI model is effective in enhancing students’ critical thinking and collaboration skills. Therefore, this model is recommended as an innovative learning alternative in the context of nonformal education and community empowerment.